PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASIONAL PIMPINAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA - Sangadji, Etta Mamang (PAEDAGOGIA, 2009)
his research aims to look at the impact of organization practice and com-mitment of organization leader toward work satisfaction and its influence to the performanceof Muhammadiyah University lecturers in East Java who have worked for above 3years. The population was 1.181 people. Random sampling was applied to get 200samples. Technique of collecting data used questionnaire, documentation, and interview.Technique of analyzing data used structural equation modeling (SEM) with Analysis atMoment Structure (AMOS) 4,01. The result of the research showed that (1) in variable oforganization practice, manifestation of risk taking did not fulfill requirement as ameasure;(2) all manifestations in organizational commitment variable were identified;(3) manifestation of achievement was not identified as a measure of work satisfactionvariable; (4) all manifestations in lecturer's performance were identified; (5) organizationpractice and commitment of organizational leader had impact directly on lecturer'sperformance;(6) organizational practice and commitment of organizational leader hadimpact directly on work satisfaction; (7) organization practice influenced directly tolecturer's performance through work satisfaction whereas commitment of organizationalleader had an impact directly on lecturer' performance through work satisfaction